2010
DOI: 10.1007/s00467-009-1291-x
|View full text |Cite
|
Sign up to set email alerts
|

The use of low-dose cyclophosphamide followed by AZA/MMF treatment in childhood lupus nephritis

Abstract: Cyclophosphamide (CYC) has been the landmark in the treatment of lupus nephritis. However, long-term treatment with CYC is associated with significant side effects. We aimed to evaluate the efficacy of short-term intravenous (IV) CYC treatment as a remission induction treatment followed by azathioprine (AZA) or mycophenolate mofetil (MMF) as a maintenance treatment. Twenty patients (18 girls) with biopsy-proven class III (5) and IV (15) lupus nephritis were included in to the study. Detailed clinical and labor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 38 publications
0
18
0
Order By: Relevance
“…However in observational studies of LN in adults rituximab has been successfully used as rescue treatment for refractory LN (78,79). Only very limited evidence for the use of rituximab for LN in cSLE was found in the literature search (37,48). Recently, an observational cohort study in cSLE reported the effects of rituximab treatment in 63 children, LN was the indication to start rituximab treatment in 36% of the patients.…”
Section: Renal Flares and Refractory Diseasementioning
confidence: 99%
See 3 more Smart Citations
“…However in observational studies of LN in adults rituximab has been successfully used as rescue treatment for refractory LN (78,79). Only very limited evidence for the use of rituximab for LN in cSLE was found in the literature search (37,48). Recently, an observational cohort study in cSLE reported the effects of rituximab treatment in 63 children, LN was the indication to start rituximab treatment in 36% of the patients.…”
Section: Renal Flares and Refractory Diseasementioning
confidence: 99%
“…In the majority of these articles I.V. CYC is used as induction treatment, with good results in the majority of patients (45)(46)(47)(48)(49)(50)(51)(52)(53). Three studies compared I.V.…”
Section: Induction Treatmentmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, the role of cyclophosphamide has been further established in pediatric non-malignant diseases such as nephrotic syndrome (Azib et al, 2011) and lupus nephritis (Baskin et al, 2010).…”
Section: Concept and Objectivesmentioning
confidence: 99%